[On Buraimi and Oman] - Barouni, Youssef El (1956)
Youssef el Barouni (a Libyan whose father Soliman Barouni Pasha was of the same Ibadi persuasion as the Omanis and had spent much time in Oman) had written to the Arab League Secretariat giving the lie to Saudi propaganda and in particular exposing the so-called Omani Ambassador. He later sent me a copy of this letter and I hope that we shall be able to make use of it.
Keywords: Relations -- Oman -- Arabie Saoudite